(untitled) (Journal of Pharmaceutical Negative Results, 2023)
A nonlocal boundary value problem for an elliptic equation is considered. The corresponding difference problem is constructed and the error of the approximate solution is estimated with a higher order of accuracy. Many applied problems in mechanics and physics [1], [2], [3], [4], [5] lead to nonlocal boundary value problems for partial differential equations. In this paper, we study a nonlocal boundary value problem for a quasilinear equation. The method of finite differences was applied to the numerical solution of the problem posed, and the error of the approximate solution of the nonlocal problem was estimated.